Prosedur Ekspor Cerutu Dengan Fasilitas Tidak Dipungut Cukai Pada Kantor Pengawasan dan Pelayanan BEA dan Cukai Tmp C Jember - Sinta Indah Lestari (Faculty of Education, 2025)
This study explores teachers’ perceptions regarding the use of authentic materials in teaching English as a foreign language (EFL) at school. Authentic materials, such as newspapers, videos, songs, and real-life texts, are believed to provide meaningful learning experiences and enhance students’ engagement with the language. The research aims to investigate how English teachers perceive the benefits, challenges, and overall effectiveness of integrating authentic materials into classroom instruction. In this research, data were collected through semi structure interviews with English teachers from Islamic senior high schools. The results indicate that most teachers hold positive perceptions of authentic materials, emphasizing their ability to increase student motivation, improve communicative competence, and provide real world context to language use. However, some challenges were also identified, including the difficulty in selecting appropriate materials for different proficiency levels and the limited time available for material adaptation. Overall, this study highlights the significant role of teacher perception in the successful implementation of authentic materials in EFL classrooms and suggests the need for further teacher training and institutional support to maximize their effectiveness.
Reupload file repositori 4 februari 2026_ratna/dea
Keywords: Teachers’ Perceptions; Authentic Materials; Teaching English